Musiikin merkitystasot musiikkiterapian teorian ja kliinisen käytännön näkökulmista - Erkkilä, Jaakko (1997)
In my dissertation, I first present a theoretical model of the different levels of meaning in the context of music therapy. Based on my clinical experience as a music therapist, I have observed that the ambiguous character of music makes it necessary to have a wide and flexible view as to the psychological frame of reference in the background of music therapy. With the help of the three-dimensional model that I have formulated, it is possible to take into account the different musical meanings in the therapeutical process with a wider view. The three-dimensional model is composed of three levels specifying musical meanings: the vitality affect level, the psycho-dynamic level, and the cognitive level. In fitting together these levels of meaning, recent research findings in the developmental psychology (mainly according to Daniel Stern [1985]), the brain dominance theory as well as the psychoanalytical theory on reformulating the primary and secondary process thinking (Eva Basch-Kahre [1985)) are utilized. After this I deal with clinical improvisation in music therapy by first defining the character of clinical improvisation and then continuing with the related methodological and interpretative possibilities. This examination is based on the theoretical frame of reference according to the three-dimensional model. Kenneth Bruscia (1987), Nordoff & Robbins and Mercedes Pavlicevic (1989) have also influenced my concepts on clinical improvisation in music therapy. As a conclusion, I present a case study of the music therapy process of an eleven-year-old boy suffering from language disorders. The main methods used in the therapy process were clinical improvisation, drawing, and cognitive-motoric rhythm and melody exercises. The therapy process proved that the holistic approach that takes into account not only the cognitive-motoric exercises (cognitive meaning level) but also creative self-expression (psycho-dynamic meaning level and vitality affect level) was justified. Moreover, it became evident that the progress achieved in the cognitive-motoric rhythm and melody exercises also influenced the clinical improvisation, adding to the expressive ways and developing interaction.